Past, present and future sea-level change in the Russian Arctic - Li, Tanghua (2022)
Accurate projection of future sea-level change in the Russian Arctic is important for navigation, coastal infrastructure, and has implications for changes in ocean circulation, ecosystems, and coastal erosion (Lamoureux et al., 2015). Accurate sea-level projection relies on an understanding of the mechanisms driving its complex evolution, which must be founded on an understanding of its history (Horton et al., 2018).